Helicity transport and dynamo sustainment for helical plasma states - R Paccagnella (New Journal of Physics, 2019)
Plasma states dominated by single helical modes are often observed in the Reverse Field Pinch (RFP) plasma confinement devices. In this paper the properties of these states are studied on the basis of a relaxation model that assumes the existence of several topological invariants related to the dominant mode. It is hypothesized that the value of the first invariant in this chain, is determined by the existence of a plasma dynamo mechanism that transport helicity. This hypothesis enables us to determine the steady state properties of the plasma equilibrium and some other interesting physical consequences. Further, by considering the properties of the transfer of helicity from the mesoscale (fluctuations) to the macroscale (equilibrium), through the dynamo field, a nonlinear dynamical model can be constructed, that evolves in time to a steady state with a non-vanishing dynamo field, when helicity is injected in the system, as in the case of the ohmic sustained RFP, while the dynamo oscillates initially, but is damped later in time, for vanishing helicity input.